Strategic assessment for managing the requirements of sustainable urban development for cities, a case study of the city of Boussaada - Dogha, Mohamed Soufiane; Zemmouri, Noureddine (Technium Social Sciences Journal, 2022)
Strategic assessment is an important tool and means for achieving sustainable urban development, as it is a scientific approach used to crystallize the developmental priorities and goals of cities, and to identify programs and projects capable of achieving these goals within a certain period of time, in line with the current and future aspirations of the population, taking into account the available resources and potential obstacles. The practical framework of the research included a review of the requirements of sustainable urban development, which contains a set of proposals for it, through the application of its evaluation in a strategic evaluation method, based on a developed reference tool proposed by the researcher and with it. Multiple scopes, which makes it possible to understand the performance of the city and determine the conditions for its sustainable urban development, and also identifies weaknesses, strengths and imbalances in the way cities behave in their application of the requirements of sustainable urban development. This tool or specification was designed by the researcher and incorporated the Delphi method In the selection of criteria, the second method is Gap analysis Which was applied to the city of Boussaada, and the results were as follows, the actual matching percentage of the recipe was 4.46%, Which indicates the existence of a non-conformity gap of 95.54%, which indicates the existence of a clear and large gap for the city of Boussaada, which is very limited, divided according to the four sections of the standard, and accordingly, after diagnosis and examination, it achieved a conformity rate of 8%, with a record size of the gap 92%, As for management and vision, it achieved a matching percentage of 7%, and accordingly, the size of the gap reached 93%, and the tools and means achieved a matching percentage of 2%, and the size of the gap was 98%. While the actions and procedures recorded a matching rate of 1%, accompanied by a gap of 99%, all this indicates that the city of Boussaada It suffers from shortcomings in its management methodology for the requirements of sustainable urban development according to the stages of preparing its plans for this, as many factors that have important effects on the sustainability of the plan in the medium and long term are neglected, and therefore it is closer to a traditional development plan that is unable to accommodate the rapid changes it is going through and the challenges it faces, which constitutes a major challenge in achieving sustainable urban development.